2014
DOI: 10.1158/1940-6207.capr-13-0262
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biochemical Studies Support Smokeless Tobacco's Carcinogenic Potential in the Human Oral Cavity

Abstract: In 2007, International Agency for Cancer Research presented compelling evidence that linked smokeless tobacco use to the development of human oral cancer. While these findings imply vigorous local carcinogen metabolism, little is known regarding levels and distribution of Phase I, II and drug egress enzymes in human oral mucosa. In the study presented here, we integrated clinical data, imaging and histopathologic analyses of an oral squamous cell carcinoma that arose at the site of smokeless tobacco quid place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…This premise is substantiated by the intracellular presence of cytochrome P450s (CYPs) capable of oxidative bioactivation of 4-HPR to 4-oxo-HPR i.e. 3A4 (consistent with human oral epithelia) and CYP26A1 [18]. Further, cell-ECM interactions are integral for both cell survival and induction of apoptosis [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This premise is substantiated by the intracellular presence of cytochrome P450s (CYPs) capable of oxidative bioactivation of 4-HPR to 4-oxo-HPR i.e. 3A4 (consistent with human oral epithelia) and CYP26A1 [18]. Further, cell-ECM interactions are integral for both cell survival and induction of apoptosis [31].…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence microscopy images were obtained by using an Olympus BX51 microscope (Olympus, Japan), NikonDS-Fi1 digital camera (Nikon, Japan) and ImagePro 6.0 (Media-Cybernetics, Bethesda, MD). Immunoblot analyses were conducted to determine presence or absence of 4-HPR metabolizing enzymes (CYPs 3A4, 2C8, 26A1) and UDP glucuronosyl transferase 1A1 (UGT1A1) in accordance with our previously published method [18]. Additional characterization studies entailed a time-course assessment of intracellular levels of 4-HPR during 4-HPR treatment with concurrent 4-HPR medium evaluation using LC-MS/MS analyses as previously described [11].…”
Section: Methodsmentioning
confidence: 99%
“…Although smokeless tobacco has long been associated with oral cancer risk, there is still a misconception of its "harmless nature" associated with the reduced tobaccorelated disease risks. 31 Nevertheless, significant variation in its composition, with varying amount of several carcinogens, associated with long-term TSNAs exposure limits the interpretation of epidemiology studies. 32 Certainly, oral leukoplakia can precede OSCC in snuff users, 28 and a recent meta-analysis of studies derived from Southern Asia demonstrated that smokeless tobacco is a risk for all PPOELs (odds ratio [OR] = 20.0; 95% confidence interval [CI] 12.3-32.5), although the risk for oral leukoplakia is not as substantial (OR = 4.33; 95% CI 1.4-13.2).…”
Section: Likely Common Risk Factors Of Potentially Malignant Oral Mucmentioning
confidence: 99%
“…A pilot human clinical trial conducted by Mallery and coworkers using a bioadhesive gel has shown that that a 6-week topical application of 10% w/v freeze-dried BRBs significantly reduced the instances of LOH in clinical premalignant lesions, and exhibited varied abilities to inhibit size and malignant progression/regression 16,18 . Very recently, Mallery and coworkers have extended the results of their pilot study in a multicenter clinical trial demonstrating reductions in lesion sizes, histologic grades, and LOH events in lesions treated with a 10% freeze-dried BRB mucoadhesive gel and identified a cohort of highly BRB-responsive individuals 31 . While there was appreciable inter-patient variation, and premalignant lesion phenotypes are subject to dynamic changes and spontaneous regression, these studies clearly support the value of a targeted topical BRB delivery strategy by decreasing the daily and cumulative BRB levels required for efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by our previous research demonstrating that 5% BRB administered in the diet reduced DNA adduct formation in the HCP 27 . Further, by scavenging ROS, these compounds inhibit ROS-mediated cellular signaling and in turn reduce unremitting proliferation 31 . In the present study, we demonstrate reduced proliferation rates in dysplasia after treatment with BRB and it can be postulated that this is due, in part, to the antioxidant effects of BRBs.…”
Section: Discussionmentioning
confidence: 99%